RELATIONSHIP BETWEEN LIFE ORIENTATION (OPTIMISM/PESSIMISM) AND MENTAL HEALTH - Taseer Fatima (Army Medical College Rawalpindi, 2019)
Objective: To study the relationship between Life Orientation (optimism/pessimism) and Mental Health.